Iwi (tribal) data collection at a primary health care organisation in Aotearoa - Matire Harwood; Vanessa Selak; Karen Brewer; Jonathan Murray; Rawiri McKree Jansen; Anneka Anderson; James (Hemi) (CSIRO Publishing, 2021)
ABSTRACT INTRODUCTIONIndigenous peoples' rights include the right to self-determine one's identity. For Māori, this includes self-assignment of ethnicity, and traditional identities such as Iwi (tribe). New Zealand's Ministry of Health requires health services to collect ethnicity data using standard protocols. Iwi data are also collected by some health services; however, with no health-specific protocols, little is known about Iwi data collection and quality. The National Hauora Coalition (NHC) Primary Healthcare Organisation (PHO) sought to understand Iwi data collection across its network of primary care providers. AIMTo understand Iwi data collection at the NHC PHO; specifically, is it being routinely collected, how is it being collected and what are the results? METHODSIn 2017, NHC's general practice clinics were invited to submit their enrolment forms, which capture ethnicity and potentially Iwi information, by e-mail to the audit team. Forms were reviewed to determine whether Iwi information was being collected and if so, what question was being used. Iwi numbers were collated from the annual data extract. RESULTSThirty-three of a total of 35 clinics (94%) submitted their enrolment forms to the audit team. Nine of the 33 clinics (27%) sought Iwi name/s with a specific question on their enrolment form. Six different 'Iwi' questions were used by the nine clinics. The data extract revealed that the NHC had Iwi data for 13% (2672/20,814) of its Māori enrolments. Ngāpuhi were the largest Iwi group at the NHC. DISCUSSIONThis is the first study to describe the quantity and quality of Iwi data collection in NZ primary care. Standard procedures for collecting, recording and using Iwi data are being developed by the NHC PHO. These could inform national protocols to optimise the quality of Iwi data.